2019
DOI: 10.32598/cjns.5.16.7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Laughter Yoga on the Quality of Life of Elderly Nursing Home Residents

Abstract: Background: Old age is associated with the physical and psychological problems that affect the Quality of Life (QoL). Objectives: This study aimed to investigate the effect of Laughter Therapy (LT) on the QoL of elderly people in nursing homes. Materials & Methods: This was a quasi-experimental study with‌ pre-test and post-test with the control and experimental group and one-month follow-up conducted in 2017. The statistical population consisted of 44 elderly people in the Mehr Aein nursing home in Astan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We, as human beings, need ontological security due to our concern about the continuation of our existence. We manage this anxiety through daily routine, social interactions, and lifestyle choices [ 26 ]. Yoga practice aims to improve or maintain physical fitness and health [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…We, as human beings, need ontological security due to our concern about the continuation of our existence. We manage this anxiety through daily routine, social interactions, and lifestyle choices [ 26 ]. Yoga practice aims to improve or maintain physical fitness and health [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained here support this statement and are consistent with those found in other research studies. These include Cornish and Wade (2015) and Kent et al (2018) , who found an improvement in psychological well-being; Rey and Extremera (2016) , an increase in life satisfaction and reduced depression; Rezaei et al (2019) , an increase in happiness and quality of life; and Sánchez-Cabaco et al (2019b ), a decrease in depression, anxiety and stress.…”
Section: Discussionmentioning
confidence: 99%